Mano Suave–Mano Dura : Legitimacy Policing and Latino Stop-and-Frisk - Rios, Victor M.; Prieto, Greg; Ibarra, Jonathan M. (American Sociological Review, 2020)
Stop-and-frisk and other punitive policing practices disproportionately affect marginalized communities of color. In response to calls for reform, police departments have implemented community policing programs aimed at improving relations with racialized communities. This study examines how a police unit used courtesy and respect in its engagement with a criminalized population, gang-associated Latinos, while relying on the stop-and-frisk practice. Our study reveals contextual and situational contradictions between modern police departments’ attempts to establish legitimacy and the hegemonic practice of investigatory stops. Drawing on observations and interviews conducted during a ride-along study, we find that stop-and-frisk, simultaneously used with reform practices like courtesy policing, yield a paradoxical policing approach, “the legitimacy policing continuum.” Officers regularly articulate a goal of respectfully interacting with courtesy to build community and trust—what we term “the mano suave”—while practicing a dominant logic of crime prevention through punitive measures—what we term “the mano dura.” We argue that community and courtesy policing are drawn on strategically in interaction and ultimately intertwined with and constrained by the racial bias at the heart of punitive policing practices like stop-and-frisk.